Il doppio ruolo di Parmenide nel Parmenide di Platone: obiettare alla teoria delle idee e portarvi aiuto come un nuovo Zenone - Giuseppe Mazzara (Peitho)
Two of the greatest interpreters of Parmenides, Giovanni Casertano and Franco Ferrari, have given opposite interpretations of the role of the character of Parmenides. For Ferrari, Parmenides would only be a critic of ideas, as he equates them with their sensitive participants (thus, he could not be considered one of the prosopa of Plato). For Casertano, on the other hand, Parmenides expresses the ‘metaphysical’ aspects of ideas in accordance with the young Socrates’ discourse on the “prodigy” in the initial part of the dialogue. Neither of the two interpretations presents a Parmenides that represents the figure of Plato adequate for the “dramatic” development of the dialogue. If, on the other hand, we regard them both as integral parts, the image and role of Parmenides could be more appropriate to the bipolar structure of the dialogue and of Plato himself. To this end, I have assumed that Plato unifies in Parmenides his dialectical-deductive method with that of Zeno: the aporetic-paradoxical one that is more open than his to finding ways of escape from any paradoxical arguments. It would be for this reason that Parmenides encourages the young and inexperienced Socrates to follow Zeno’s tropos when defining virtue, also because it was Socrates himself, in the final part of his discourse on the “prodigy,” who praised Zeno for the double courage shown first in criticizing the common sense and the principles of current physics and then in overcoming the contrast between these principles and the more specific mathematizing logic. I identify in this praise of Socrates an assumption, on the part of Parmenides, that the burden of bringing back into ideas the courageous behaviour that Zeno showed in the world of the sensible. I agree with Vlastos in considering Parmenides to be “the manifesto of Plato’s self-criticism,” and in viewing this Parmenides as the prosopon of a Plato that is willing both to level self-criticism at his own stance and to give voice to those who do not think like him and even to those who reject his position.